Определение вероятности снижения адаптационных возможностей у подростков с сердечно-сосудистыми заболеваниями - Высоцкая, Е. В.; Рак, Л. И.; Порван, А. П.; Цапенко, К. В.; Гаврюшина, Е. А. (My University, 2016)
Работа посвящена определению вероятности снижения адаптационных возможностей у подростков с сердечно-сосудистыми заболеваниями и синтезу математической модели с использованием метода бинарной логистической регрессии, которая позволит повысить эффективность выявления нарушений адаптации у детей и подростков за счет комплексной оценки показателей работы сердечно-сосудистой и вегетативной нервной систем, отражающих общее физического состояния ребенка. Использование предложенного подхода даст возможность своевременно проводить коррекцию лечения и реабилитации подростков с наиболее частыми в педиатрии вторичными кардиомиопатиями. Робота присвячена визначенню ймовірності зниження адаптаційних можливостей у підлітків із серцево-судинними захворюваннями і синтезу математичної моделі з використанням методу бінарної логістичної регресії, яка дозволить підвищити ефективність виявлення порушень адаптації у дітей та підлітків за рахунок комплексної оцінки показників роботи серцево-судинної і вегетативної нервової систем, що відображають загальний фізичний стан дитини. Використання запропонованого підходу дасть можливість своєчасно проводити корекцію лікування та реабілітації підлітків з найбільш частими в педіатрії вторинними кардиомиопатиями. The article is devoted to determining the probability of reducing the adaptive capabilities of teenagers with cardiovascular diseases and synthesis of mathematical model using the method of binary logistic regression, which will increase the efficiency of identifying adaptation disorders in children and adolescents due to a comprehensive assessment of performance of the cardiovascular and autonomic nervous systems, reflecting the overall physical condition of the child. According to the received model, the increase in diastolic blood pressure may occur along with increased overall weight and size of a growth indicator and the left ventricle. Therefore, a significant change in the parameters of physical development in the direction of increasing the mass of the body of a teenager and, accordingly, heart is not accompanied by an increase in left ventricular mass, impair the functional reserves of the heart and the adaptive capacity of the organism as a whole. The synthesized mathematical model is adequate and the qualitative and allows to identify 94.7 % of the decrease in adaptive capabilities of teenagers with heart disease. Using the proposed approach will enable a timely manner to carry out the correction of treatment and rehabilitation of teenagers with the most common pediatric secondary cardiomyopathies.
Keywords: вторичные кардиомиопатии; логистическая регрессия; частота сердечных сокращений; ЧСС; артериальное давление